Effect of disease duration and other characteristics on efficacy outcomes in clinical trials of tocilizumab for rheumatoid arthritis. (26th August 2020) - Rubbert-Roth, Andrea; Aletaha, Daniel; Devenport, Jenny; Sidiropoulos, Paris N; Luder, Yves; Edwardes, Michael D; Jacobs, Johannes W G
Abstract: Objective: To determine the extent to which disease duration, alone or in combination with other baseline clinical and non-clinical factors, explains variations in outcome of tocilizumab initiated in biologic-naïve patients with established RA. Methods: In this pooled analysis of phase 3 and 4 clinical trials conducted by the sponsor, predictors of response, including demographics, disease characteristics at baseline (start of tocilizumab dosing) and study characteristics (e.g. patient inclusion criteria, tocilizumab dosing regimen) were evaluated. Response was measured as change from baseline to week 24 in Clinical Disease Activity Index (CDAI) and HAQ–Disability Index (HAQ-DI) scores and as the proportions of patients who experienced ≥50% improvement based on ACR criteria (ACR50) and CDAI remission (≤2.8) rates at week 24. Results: Improvements in all outcomes investigated were observed in patients receiving tocilizumab. Although disease duration was statistically significant in the models, it accounted for <2% of variation in CDAI and HAQ-DI score changes from baseline to week 24; baseline CDAI and HAQ-DI values accounted for 32% and 15% of variations, respectively. Doubling of disease duration reduced the odds of achieving an ACR50 response by only 9%, and each additional 5-year period of disease duration decreased the odds of achieving CDAI remission by only 15%. Conclusion: RA duration, alone or in combination with other baseline characteristics, had a statistically significant but clinically small effect on the outcomes of tocilizumab initiated in biologic-naïve patients with established RA.